MODAL SOSIAL DAN STRATEGI NAFKAH (STUDI KASUS) RUMAH TANGGA PETANI MASYARAKAT SUKU DANI DI DUSUN KALI MERAH KAMPUNG KALISEMEN DISTRIK NABIRE BARAT KABUPATEN NABIRE - Hans F Liborang (Fakultas Pertanian dan Peternakan, 2020)
The purpose of this study was to determine the Household Livelihood Strategy and Social Capital used by the Dani Tribe Farming Community in Kali Merah Hamlet, Kalisemen Village, West Nabire District, Nabire Regency. The location of this research is Kali Merah Hamlet, Kalisemen Village, West Nabire District, Nabire Regency, which was carried out from November 2021 to March 2022. This research approach was carried out with a qualitative approach, with the types of data used were quantitative data and qualitative data. The data collection method in this study used the principle of triangulation in the form of interviews, observations, and document analysis. The results of this study indicate that: (1). The social capital used by Dani farmer households is bound and exclusive (bonding social capital). (2). Natural capital (natural capital) and human capital can be met from the use of social capital first. (3). Financial capital will strengthen social capital in their household livelihood strategies.